2014
DOI: 10.1063/1.4891305
|View full text |Cite
|
Sign up to set email alerts
|

Modeling kinetics and equilibrium of membranes with fields: Milestoning analysis and implication to permeation

Abstract: Coarse graining of membrane simulations by translating atomistic dynamics to densities and fields with Milestoning is discussed. The space of the membrane system is divided into cells and the different cells are characterized by order parameters presenting the number densities. The dynamics of the order parameters are probed with Milestoning. The methodology is illustrated here for a phospholipid membrane system (a hydrated bilayer of DOPC (1,2-dioleoyl-sn-glycero-3-phosphocholine) lipid molecules). Significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 107 publications
1
50
0
Order By: Relevance
“…25 Previous studies of tryptophan using the more advanced method of milestoning report permeation times on the time scale of hours, which are also in agreement with experimental results. 43,44,85,86 Most other studies have also reported much larger and faster permeability coefficients using the inhomogeneous solubilitydiffusion model, which has been discussed in great detail in other works. 18,25,43,44,[87][88][89] Several assumptions underpin the solubility-diffusion model, including memoryless, diffusivetype motion along the reaction coordinate and the presence of only one slow variable describing the motion of the permeant-namely, the translocation along the membrane normal.…”
Section: Permeability Measuresmentioning
confidence: 98%
See 2 more Smart Citations
“…25 Previous studies of tryptophan using the more advanced method of milestoning report permeation times on the time scale of hours, which are also in agreement with experimental results. 43,44,85,86 Most other studies have also reported much larger and faster permeability coefficients using the inhomogeneous solubilitydiffusion model, which has been discussed in great detail in other works. 18,25,43,44,[87][88][89] Several assumptions underpin the solubility-diffusion model, including memoryless, diffusivetype motion along the reaction coordinate and the presence of only one slow variable describing the motion of the permeant-namely, the translocation along the membrane normal.…”
Section: Permeability Measuresmentioning
confidence: 98%
“…18,43,44,87,89,90 Others hypothesize that membrane and solvent structural fluctuations play an important role as well. 39,85 The CHARMM lipid force field also overestimates the electric field strength within the membrane by a factor of 3, which may be lowering the value of the PMF within the membrane interior and subsequently accelerating the mean passage time. 63 The discrepancy between our experimental and theoretical results can be attributed to any or all of the above concerns.…”
Section: Permeability Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The force field used for the DOPC molecules was the united-atom Berger force field 47 for the acyl chain atoms and OPLS 46 for the head groups; this set up was the same as used in. 48 …”
Section: Numerical Examplesmentioning
confidence: 99%
“…In a recent paper 25 we discussed an analysis of membrane and permeation dynamics using atomically detailed simulations and the theory of Milestoning. Milestoning translates particle dynamics to the dynamics and equilibrium of densities in coarse space.…”
Section: Introductionmentioning
confidence: 99%